Rise of an empire: analyzing the high diversity of the earliest sauropodomorph dinosaurs through distinct hypotheses. (25th November 2020) - Müller, Rodrigo T.; Garcia, Maurício S.
ABSTRACT: Several new early sauropodomorphs have been described from Carnian South American strata that include the oldest unambiguous dinosaurs worldwide. Hence, these findings suggest a high diversity in the origin of the group. Here we offer three hypotheses based in novel data that can explain this diversity at the first branches of the long evolutionary tree of the sauropodomorphs. The first hypothesis explains that the Triassic specimens excavated from Brazilian strata are not coeval owing to the lack of stratigraphic control. Fortunately, new studies are constraining the age of Triassic outcrops from Brazil. The second hypothesis suggests an overstated diversity in response to the unknown ontogenetic pathways adopted by early dinosaurs. This hypothesis still demands new findings in order to clarify these ontogenetic pathways. The third hypothesis supports a high diversity in the same time span in response to distinct ecological roles adopted by the early sauropodomorphs. Indeed, there are specimens with different tooth morphologies, indicating diverse feeding strategies. This hypothesis is supported in an ecomorphological analysis derived from discrete anatomical traits. Therefore, although facing many conflicting questions regarding alpha taxonomy of Carnian sauropodomorphs, new discoveries and alternative approaches are leading towards a better understanding of the early evolution of Sauropodomorpha.